2018
DOI: 10.17650/1726-9776-2018-14-3-17-24
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of Matrix Metalloproteinase 9 in Renal Cell Carcinoma

Abstract: Objective: to assess matrix metalloproteinase 9 (MMP-9)  expression in renal cell carcinoma cells and cells of intratumoral inflammatory infiltrates depending on clinical and morphological characteristics and postoperative survival.Materials and methods. We evaluated MMP-expression in 108 renal cancer tissue specimens. The intensity of immunohistochemical staining was estimated by measuring integral optical density in cytoplasm.Results. We found that the integral optical density of MMP-9 immunostaining in tumo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 9 publications
1
2
1
Order By: Relevance
“…An individual analysis revealed a decrease in CA9 by 2.5–5.5 times in 70% of the examined patients on the 8–9 th day after the radical operation. These results confirm the existing assumption [ 10 , 13 ] about the predominant production of CA9 by tumor cells.…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…An individual analysis revealed a decrease in CA9 by 2.5–5.5 times in 70% of the examined patients on the 8–9 th day after the radical operation. These results confirm the existing assumption [ 10 , 13 ] about the predominant production of CA9 by tumor cells.…”
Section: Resultssupporting
confidence: 92%
“…Avdoshin et al [ 17 ] reported differences between urothelial carcinomas of low and high malignancy in terms of expression of MMP9. It should be noted that the decrease in serum MMP9 with increasing tumor sizes or with decreasing tumor differentiation does not corroborate with the expression of MMP9 in tumor cells as reported by others [ 10 ]. Despite the increased proliferation of tumor cells together with MMP9 production, a significant part of MMP9 may still be utilized locally within the malignant cells (for proteolysis of membrane proteins, invasion of tumor cells into the underlying tissues, or neo-angiogenesis) and not reach the bloodstream.…”
Section: Resultscontrasting
confidence: 53%
See 2 more Smart Citations